Two Decades Rituximab Therapy in Anti-Neutrophil Cytoplasmic Antibody Associated Vasculitis - Habibi, Mohammad Amin; Ahmadpour, Sajjad; Tafaroji, Javad; Eazi, Seyed Mohammad; Minaee, Poriya; Mohammadpour, Yousef; Tavakolpour, Soheil (Current Drug Targets, 2025)
Remission failure and relapse numerate as one of the main problems in patients with antineutrophil cytoplasmic antibody-associated vasculitis (AAVs). The need for new agents that provide effective and safe induction accompanied by sustained remission seems to be urgent in clinical care. The efficacy and safety of rituximab (RTX) for AAVs therapy has been reported in various studies. RTX therapy offers several advantages to treating AAVs patients compared to other therapeutic approaches including reduction of Glucocorticoids (GCs) and conventional Immunosuppressive therapy (IST) usage during both the induction of remission and maintenance phases. This reduction can lead to a lower rate of serious complications making RTX therapy a safer option. It seems that RTX may provide improved clinical outcomes in these patients mediated via B-lymphocyte depletion, Proteinase 3-antineutrophilic cytoplasmic antibody (PR3-ANCA), and myeloperoxidase-antineutrophilic cytoplasmic antibody (MPO-ANCA) titers reduction. In this regard, some uncertainties have been reported to validate the association between such depletion and clinical improvement, as suggested by other sources of autoreactive B cells that did not target with RTX. Due to the prolonged B cell depletion, fixed intervals and adjusted dosage of RTX may be required in patients with AAVs. In this narrative review, we aimed to insight better understand regarding the efficacy of RTX for effective induction and sustained remission in patients with AAVs. It seems that discovering new biomarkers predicting relapse in AAVs patients can lead to future targeted therapy.
Keywords: Rituximab